A COMPARATIVE REVIEW OF ENGLISH TEXTBOOKS FOR TENTH-GRADE STUDENTS ‘BAHASA INGGRIS: WORK IN PROGRESS’ AND ‘ENGLISH IN MIND BOOK 3’ - Homanfil Atori Nurislami Wilman; Desvalini Anwar (University of Kuningan, 2025)
This study evaluates English textbooks used in Indonesian high schools to determine their alignment with curriculum standards and their effectiveness in supporting language acquisition. Using document analysis, textbooks were assessed based on key criteria, including aims and approaches, design and organization, language content, skills development, topics and cultural representation, and practical considerations. A Likert-scale rating (1–4) was applied to quantify evaluation results. The findings highlight strengths and weaknesses in locally produced textbooks compared to internationally published materials, emphasizing the need for improvements in cultural inclusivity, skills integration, and real-life applicability. The results provide valuable insights for educators, curriculum developers, and policymakers in selecting and enhancing English learning resources. Additionally, the study serves as a reference for future research on textbook evaluation, particularly in adapting global materials to local educational contexts. By identifying gaps and providing recommendations, this research contributes to the continuous development of high-quality textbooks that align with national and international standards, ultimately improving English language education in Indonesia.